The Effect of User Generated Content and Promotion Mediated By Influncer on Purchasing Decisions (Study on Shopee Users in Majalengka Regency) - LM, L Suparto; Engkun Kurnadi; R Neny Kusumadewi; Dina Ristiana (Finance and Business Management Journal, 2024)
Technology is currently experiencing very rapid development, especially the use of the internet. The internet has encouraged the improvement of communication technology, media, and informatics which has an influence on the ways and patterns of business activities of the trade industry. This increase in the internet has also encouraged the development of digital marketing strategies by companies to increase consumer purchasing decisions. This study aims to empirically examine the effect of user generated content, promotion and influencers on purchasing decisions, and influencer mediation on the influence of user generated content and promotion on purchasing decisions. The population of this study were Shopee E-Commerce consumers in Majalengka Regency. The sample taken was 100 people, the sampling technique used purphosive sampling. Data was collected using a questionnaire, which was distributed via whatapps social media. Data analysis techniques using Structural Equation Model Partial Least Square (SEMPLS). Endogenous variables consist of user generated content and promotion, mediating variables are influencers and exogenous variables are purchasing decisions. The results of the analysis show that the results of this study indicate that user generated content (UGC), and influencers have a direct influence on purchasing decisions while promotions have no direct effect on consumer purchasing decisions. User generated content (UGC) and promotion have a direct influence on influencers. Influencers mediate the influence of user generated content (UGC) on purchasing decisions, but influencers do not mediate the influence of promotions on purchasing decisions